Dietary Intakes, Knowledge of People about the Diseases and Nutritional Disorders in two Desert Districts of Rajasthan - Ramnath, T; Ganguly, K K; Mahapatra, A; Yadav, Sheshpal; Pandey, R M (Annals of Arid Zone, 2016)
Comprehensive health survey was initiated in 1986, in two desert districts of Rajasthan covering 512 households from 19 villages and 438 households from 15 villages from Jodhpur and Bikaner districts respectively. The results show that more than 30 %of the families have to travel more than 10 km to avail any health facilities. More than 50 % of the respondents had the knowledge of fever, diarrhoea, worm infestation, measles, malaria and guinea worm. However, their knowledge about nutritional disorders was poor in both the districts. The diets were predominantly based on bajra and wheat.Theconsumption of pulses,vegetables, fats and oil, sugar and other foods were far from satisfactory and were below 30 g. The nutrients intake (except protein) were inadequate in all the age groups but the deficits of nutrients were observed to be more pronounced among childern below 12 years.